EVALUATION OF ANTIMICROBIAL ACTIVITY AND PHYTOCHEMICAL ANALYSIS OF PAPAYA AND PINEAPPLE FRUIT JUICES AGAINST SELECTED ENTERIC PATHOGENS - BANSODE D.S.; CHAVAN M.D. (International Journal of Pharma and Bio Sciences, 2013)
In recent years multiple resistances in human pathogenic microorganisms have developed due to indiscriminate use of antibiotic drugs commonly employed in the treatment of infectious diseases. The objective of present study was to evaluate antimicrobial activity and phytochemical analysis of fruit juices of Papaya (Carica papaya) and Pineapple (Ananas comosus) against medically important selected enteric pathogens. The Papaya and pineapple fruit juices were subjected to screening against enteric pathogens E.coli, Salmonella paratyphy B, and Shigella sonnei. Antimicrobial analysis was done by using the agar well diffusion method against selected enteric bacteria. The MIC values were determined by using U.V. Spectrophotometer. The fresh crude Pineapple fruit juice produced the highest antimicrobial activity against E.coli followed by Shigella sonnei and Salmonella para.B. and fresh crude Papaya fruit juice produced the highest antimicrobial activity against Shigella sonnei followed by E.coli and Salmonella para.B. The phytochemical analysis showed presence of protein, carbohydrate, flavonoids, glycosides, steroids and reducing sugar. The antimicrobial activity of standard antibiotic Ampicillin was studied in comparison with papaya and pineapple fruit juices.The Ayurvedic system of medicine has described various fruit juices in the treatment of diseases, which play an important role in modern health care and curing various ailments and diseases. The uses of herbal medicines are increasing as a dietary supplement to fight or prevent common diseases. It has great demand for primary health care because plant based medicines; health product, pharmaceuticals, food supplements, cosmetics etc. are thought to be non toxic, have less side effects and easily available at affordable cost .There are several reports on antimicrobial activity of crude fruit juices that inhibits various bacteria. However limited number of antimicrobial activity of in vitro studies on various fruit juices has been published, it has not been determined whether they are superior or equivalent to antibiotics. Therefore scientific evaluation of these fruit juices is the need of hour to check their antimicrobial activity and supports their use as an alternative medicine in the treatment of enteric infections. Hence an attempt was made, to screen the antimicrobial analysis and phytochemical study of fresh fruit juices of Papaya and Pineapple in the prevention of enteric bacterial infections.